Genes for editing to improve economic traits in aquaculture fish species - Zituo Yang; Guihong Fu; May Lee; Shadame Yeo; Gen Hua Yue (Aquaculture and Fisheries)
Aquaculture, a critical sector for global food security, faces the challenge of meeting growing demand while protecting wild fish populations. Gene editing, a powerful genetic tool, emerges as a potential solution. By modifying key genes in fish, it is expected to rapidly enhance growth rate, disease resistance, and other economically important traits, leading to increased profitability, sustainability, and competitiveness of the industry. This review navigates the complex landscape of genes for important traits, gene editing in aquaculture, exploring successes, challenges, and prospects for improved productivity, sustainability, and resilience. We provide guidance for researchers and stakeholders in identifying and editing genes responsible for important traits, while addressing economic, environmental, regulatory, and ethical considerations. This roadmap paves the way for a future where gene editing empowers aquaculture to meet global food needs while upholding environmental responsibility.